A Study Maintenance and Production Problems in Two of Cement Factories in Libya by Using TPM (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The principle of this paper is to investigatemaintenance and production problems in the cement factory in Libya with particular emphasis on Total ProductiveMaintenance (TPM). The paper presents the use of casestudy approach of production data and history, field visits.There is no clear TPM strategy and it has been also foundthat the lack of training and personal development is themain cause of this problem. In addition, employees arefound not to be motivated as a result of the lack of poormanagement strategy and reward structure. Based on thefindings, a new framework for TPM has been developed.This TPM strategy could be implemented in other Libyanfactories as a result of the potential similarities in thecultural and environmental aspects. The comparativeanalysis is developed into a model for international strategydesign and implementation. The paper highlights limitationis the cement factories in Libya in relation to TPM andproduction strategies. The importance of adopting arealistic strategy and framework by managers is discussed.This work is developed as collaboration between Academiaand Libyan Cement industry for solving productivityproblems and develop a strategic framework of TPM forimproving the Libyan industry.